Driving Distance and Food Accessibility: A Geospatial Analysis of the Food Environment in the Navajo Nation and Border Towns - Bennion, Natalie; Redelfs, Alisha H.; Spruance, Lori; Benally, Shelby; Sloan-Aagard, Chantel (Frontiers in Nutrition, 2022)
The Navajo Nation, an area home to approximately 173,000 people in the southwest United States, experiences the highest rates of food insecurity in the United States and is classified as a food desert. The present study assessed the accessibility to food outlets (grocery stores, convenience stores, and restaurants) as measured by driving time on the Navajo Nation and in selected surrounding border towns. Food outlets located in neighboring border towns were examined using network analysis tools in ArcGIS Pro to calculate driving distance and examine the potential impact of driving time within the Navajo Nation on accessibility to nutritious foods. There were 14 grocery stores, 21 convenience stores, and 65 restaurants identified in the Navajo Nation using Mergent Intellect, a proprietary database, as compared to border towns which had a total of 542 grocery stores, 762 convenience stores, and 3,329 restaurants equaling a ratio of about 50:1 (grocery, 39:1; convenience, 36:1; restaurants, 51:1) when comparing food outlets nearby versus on the Navajo Nation. This ecological study presents a visual representation of driving time and food accessibility, revealing geographic areas within the Navajo Nation where access to border town food stores is sparse, and food insecurity may be elevated.